Anthracycline-induced cardiotoxicity: mechanisms, monitoring, and prevention - Qiu, Yun; Jiang, Piao; Huang, Yingmei (Frontiers in Cardiovascular Medicine, 2023)
Anthracyclines are the most fundamental and important treatment of several cancers especially for lymphoma and breast cancer. However, their use is limited by a dose-dependent cardiotoxicity which may emerge early at the initiation of anthracycline administration or several years after termination of the therapy. A full comprehending of the mechanisms of anthracycline-induced cardiotoxicity, which has not been achieved and is currently under the efforts, is critical to the advance of developing effective methods to protect against the cardiotoxicity, as well as to early detect and treat it. Therefore, we review the recent progress of the mechanism underlying anthracycline-induced cardiotoxicity, as well as approaches to monitor and prevent this issue.